Effects of Vachellia mearnsii Tannin Extract as an Additive on Fermentation Quality, Aerobic Stability, and Microbial Modulation of Maize Silage - Thamsanqa Doctor Empire Mpanza; Sinalo Mani (Microorganisms, 2023)
Maize silage is produced to alleviate the effects of forage shortages on ruminant animals, particularly during the dry season. Microorganisms play a significant role in silage fermentation and thus, to a large extent, determine the silage quality. The modulation of silage microorganisms may help to inhibit undesirable bacteria and improve the silage quality. Therefore, condensed tannin extract from Vachellia mearnsii bark was used as an additive in maize silage during ensiling. Hence, this study evaluated the effects of a tannin extract (condensed tannin) additive on the fermentative quality, aerobic stability, and bacterial composition of maize silage. A mini-silo experiment on maize with five treatments was conducted for 75 days. The silage treatments were as follows: (T1) maize forage with no inoculation (negative control); (T2) maize forage inoculated with LAB and 1% tannin extract; (T3) maize forage inoculated with LAB only (positive control); (T4) and maize forage inoculated with LAB and 2% tannin extract; (T5) maize forage inoculated with LAB and 3% tannin extract. The results showed that the additives modulated the silage microorganism composition. However, this was without affecting the silage’s fermentative quality and aerobic stability. All the silages recorded a pH below 4.2, which indicated well-fermented silage. The tannin extract suppressed the growth of undesirable bacteria, such as Dysgonomonas, Gluconacetobacter and Clostridium genera, while promoting desirable bacteria, such as Lactobacillus and Weissella genera, which were attributed to the silage quality. It is thus concluded that tannins can be strategically used as silage additives to modulate the microbial composition of silage and improve the silage quality by promoting the dominance of the desirable bacteria in the silage.